Palladium-Catalyzed ortho-Acylation of 2-Aryl-1,2,3-triazoles with Toluene Derivatives - He, Ping; Tian, Qingshan; Kuang, Chunxiang (Synthesis, 2015)
A palladium-catalyzed ortho-acylation of 2-aryl-1,2,3-triazoles was developed in which low-toxicity, stable, commercially available toluene derivatives were used as acyl sources. A wide variety of aryl ketones containing 1,2,3-triazoles were obtained in moderate to excellent yields. A plausible mechanism is proposed.
Keywords: palladium; catalysis; acylations; triazoles; ketones